1997
DOI: 10.1074/jbc.272.38.23559
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-like Activity and Temperature-induced Structural Changes of α-Crystallin

Abstract: ␣-Crystallin is known to exhibit chaperone-like activity. We have studied its chaperone-like activity toward the aggregation of ␤ L -crystallin upon refolding of this protein from its unfolded state in guanidinium chloride. The chaperone-like activity of ␣-crystallin is less pronounced below 30°C and is enhanced above this temperature. The plot of percentage protection as a function of temperature shows two transitions; one at 30°C and another at around 55°C. We have performed steady state fluorescence, fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
133
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(148 citation statements)
references
References 45 publications
14
133
1
Order By: Relevance
“…Hydrophobic sites in α-crystallin are thought to be responsible for its chaperone activity [45,[134][135][136][137] and hydrophobic peptides isolated from αA-crystallin (residues 70-88) [137] and αB-crystallin (residues 73-92 and 131-141) [24, 138] possess chaperone activity against amorphously aggregating target proteins. The chaperone activity of these peptides results from their ability to bind independently to target proteins [137].…”
Section: The Region(s) Of α-Crystallin Responsible For Target Proteinmentioning
confidence: 99%
“…Hydrophobic sites in α-crystallin are thought to be responsible for its chaperone activity [45,[134][135][136][137] and hydrophobic peptides isolated from αA-crystallin (residues 70-88) [137] and αB-crystallin (residues 73-92 and 131-141) [24, 138] possess chaperone activity against amorphously aggregating target proteins. The chaperone activity of these peptides results from their ability to bind independently to target proteins [137].…”
Section: The Region(s) Of α-Crystallin Responsible For Target Proteinmentioning
confidence: 99%
“…By using various non-thermal modes of aggregation, it was shown that chaperone-like activity of ␣-crystallin is temperature-dependent. A structural perturbation above 30°C enhances this activity severalfold (6,7). In order to probe the molecular mechanism of the chaperone-like activity and its enhancement upon structural perturbation, we have been studying ␣-crystallin and its constituent subunits.…”
mentioning
confidence: 99%
“…A structural transition above 30°C enhances the protective ability perhaps by increasing or reorganizing hydrophobic surfaces. We have recently shown that tertiary structural changes precede quaternary structural changes (20,21). ␣-Crystallin is a heteroaggregate of two gene products, ␣A-and ␣B-crystallin.…”
mentioning
confidence: 99%